Application of Waterfall Method in Sales System using Laravel 10 Framework in Bella Grocery Store - Fernanda Bagus Dwi Prastyo; Abdul Rohman (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
Bella grocery store does not yet have a cashier system that can record transactions and manage stock items so it faces various challenges in managing stock items and recording transactions. Our research aimed to build a web-based sales system at the store using the waterfall method and the Laravel 10 framework. To identify the main needs including stock management, transaction recording and financial reports we collect data through direct interviews and observations. The system is designed with the waterfall method starting from requirements analysis, system design, and implementation to testing.  The results of the implementation of this system can help manage stock items, and record transactions and financial reports at the store. The results of black box testing ensure that all features function properly. with this system, Bella grocery stores can manage stores more accurately and organized.